Experimental and theoretical evidence of attractive interactions between dianions: [PdCl4]2−⋯[PdCl4]2−. Issue 98 (22nd November 2021) - Zierkiewicz, Wiktor; Michalczyk, Mariusz; Maris, Thierry; Wysokiński, Rafał; Scheiner, Steve
Abstract : It is demonstrated that even dianions, each with charge −2, can establish attractive interactions with one another. Abstract : Inspection of the arrangement of tetrachloridopalladate(ii ) centers in a crystalline solid places the Cl of one [PdCl4 ] 2− directly above the Pd center of its neighbor. A survey of the CSD provides 22 more examples of such MX4 2− ⋯MX4 2− complexes, with M being a Group 10 metal and X = Cl, Br, or I. Quantum calculations attribute this arrangement to a π-hole bond wherein Cl lone pairs of one unit transfer charge to vacant orbitals above the Pd center of its neighbor. The stabilizing effect of this bond must overcome the strong Coulombic repulsion between the two dianions, which is facilitated by a polarizable environment as would be present in a crystal, but much more so when the effects of the neighboring counterions are factored in. These conclusions are extended to other [MX4 ] 2− homodimers, where M represents other members of Group 10, namely Ni and Pt.